Seropositivity and flight-associated risk factors for SARS-CoV-2 infection among asylum seekers arriving in Berlin, Germany – a cross-sectional study - Brandt, Ariadne; Breucker, Lena; Keller, Jan; Corman, Victor Max; Bethke, Norma; Seybold, Joachim (Frontiers in Public Health, 2023)
Refugees and asylum seekers might be at increased risk of SARS-CoV-2 infection due to precarious living conditions during flight. Between March 24th and June 15th 2021, we conducted a cross-sectional study in adult asylum seekers arriving in Berlin. Each participant was tested for acute SARS-CoV-2 infection with a nasopharyngeal swab using reverse transcriptase PCR (rt-PCR), and for anti-SARS-CoV-2-S1 IgG antibodies using ELISA. Seropositivity, antibody avidity, and data on flight history were used to categorize individuals into two groups according to the estimated time of infection before or during flight. Sociodemographic characteristics, COVID-19 related symptoms, hygiene behaviours, and living conditions during transit were assessed using two self-report questionnaires. Among 1041 participants (34·5% female, mean age 32·6 years), most frequently reported countries of origin were Moldova (20·5%), Georgia (18·9%), Syria (13·0%), Afghanistan (11·3%), and Vietnam (9·1%). Seropositivity rate was 25·1% and incidence rate of acute SARS-CoV-2 infection was 2·8%. A higher likelihood for seropositivity was observed in women (OR [95%CI]=1·64 [1·05-2·57]) but reduced by frequent hygiene behaviours (OR [95%CI]=0·75 [0·59-0·96]) or travelling by plane (OR [95%CI]=0·58 [0·35-0·96]). Other associated factors were lower educational level, accommodation in refugee shelters, travelling with children or by foot, and COVID-19 information seeking. Flight-associated risk factors such as accommodation in a refugee shelter and poor hygiene behaviours are associated with an elevated risk of infection, which should be addressed by public health interventions. Trial registration ISRCTN registry (Trial number: 17401860, https://doi.org/10.1186/ISRCTN17401860)